2018
DOI: 10.1371/journal.pone.0204721
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of lung toxicity risk with computed tomography ventilation image for thoracic cancer patients

Abstract: BackgroundFour-dimensional computed tomography (4D-CT) ventilation is an emerging imaging modality. Functional avoidance of regions according to 4D-CT ventilation may reduce lung toxicity after radiation therapy. This study evaluated associations between 4D-CT ventilation-based dosimetric parameters and clinical outcomes.MethodsPre-treatment 4D-CT data were used to retrospectively construct ventilation images for 40 thoracic cancer patients retrospectively. Fifteen patients were treated with conventional radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…They determined that the best predictors of RILT based on ROC analysis were the mean dose, V20Gy, and V5Gy within the poorly ventilated regions. 18 It is important to reiterate that during this current work, regions of 20 Gy dose in the abnormal function PRM contours were not funneled to other regions of the lung that had more normal function, as previously described, which is shown by the significant V20Gy and mean dose decreases in Table 3 . Also, one could feasibly customize the workflow from this study to avoid regions of normal lung function.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…They determined that the best predictors of RILT based on ROC analysis were the mean dose, V20Gy, and V5Gy within the poorly ventilated regions. 18 It is important to reiterate that during this current work, regions of 20 Gy dose in the abnormal function PRM contours were not funneled to other regions of the lung that had more normal function, as previously described, which is shown by the significant V20Gy and mean dose decreases in Table 3 . Also, one could feasibly customize the workflow from this study to avoid regions of normal lung function.…”
Section: Discussionsupporting
confidence: 76%
“…[15][16][17] Furthermore, some recent studies have found that a lower functioning lung appears inherently more susceptible to radiation. 15,18 The works of both Otsuka et al and Owen et al found that the volume receiving greater than or equal to 20 Gy (V20Gy) in regions of poor lung function showed high predictive power of a patient's RILT risk, suggesting that the dose to low function regions should be mitigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Similarly, in 2018, Otsuka et al published a study that concluded that a high dose to poorly functioning regions, as determined by 4-dimensional CT V, was associated with the highest risk of toxicity. 53 However, dysfunctional lung sensitivity to RT has never been shown on V/Q SPECT imaging.…”
Section: Structurementioning
confidence: 99%
“…Studies have shown that dose-function metrics are more predictive of radiation toxicity than dose alone (33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%